计算机代写 discrete mathematics Hoare Logic: Total Correctness – cscodehelp代写

Hoare Logic: Total Correctness
COMP1600 / COMP6260
Australian National University
Semester 2, 2021
1/49

Recall: Hoare Logic
Basic Ingredient. Hoare-triples
{P} S {Q}
P and Q are predicates (formulae) S is a code (fragment)
Example. {x > 0} while (x>0) do x := x-1 {x = 0}
Meaning. If we run S from a state that satisfies precondition P and if S terminates, then the post-state will satisfy Q.
1/49
1/49

Hoare Logic
Idea. Proof Rules that allow us to prove all true triples. Assignment
{Q(e)} x := e {Q(x)} Precondition Strengthening / Postcondition Weakening
Ps →Pw {Pw}S{Q} {Ps} S {Q}
{P}S{Qs}
{P} S {Qw}
{P} S1 {Q}
{P}S1;S2 {R}
{P ∧b} S1 {Q} {P ∧¬b} S2 {Q} {P}ifbthenS1 elseS2{Q}
Qs →Qw
Sequence.
Conditional.
{Q} S2 {R}
2/49
2/49

Proof Rule for While Loops (Rule 6/6)
{I∧b} S {I}
{I} while b do S {I∧¬b}
I is called the loop invariant.
I is true before we encounter the while statement, and remains true each time around the loop (although not necessarily midway during execution of the loop body).
If the loop terminates the control condition must be false, so ¬b appears in the postcondition.
For the body of the loop S to execute, b needs to be true, so it appears in the precondition.
3/49
3/49

Soundness of the While Rule w.r.t. the semantics
{I∧b} S {I}
{I} while b do S {I∧¬b}
Soundness. If the premise is true, then so is the conclusion.
assume that I holds in the initial state.
if b is false, nothing happens, so I ∧ ¬b is true in post-state.
if b is true, then (by premise) I holds at end of each iteration assuming that the loop terminates, b becomes false (and I still holds)
Q. What about non-termination?
4/49
4/49

Applying the While Rule
{I∧b} S {I}
{I} while b do S {I∧¬b}
{P} while b do S {Q}
Difficult bit. Finding the right invariant.
This requires intuition and practice. There is no automated way of
doing this.
Easy bit. Establishing the desired postcondition
The postcondition we get after applying our rule has form I ∧ ¬b. But if I ∧ ¬b → Q, we can use postcondition weakening.
Easy bit. Establishing the desired precondition
The precondition we get after applying our rule has form I. But if P → I , we can use precondition strengtening.
5/49
5/49

Applying the While Rule (schematic proof)
{I∧b} S {I}
{I} while b do S {I∧¬b}
{P} while b do S {Q}
6/49
6/49

Applying the While Rule (schematic proof)
{I∧b} S {I}
{I} while b do S {I∧¬b}
{P} while b do S {Q}
{P} while b do S {Q}
6/49
6/49

Applying the While Rule (schematic proof)
{I∧b} S {I}
{I} while b do S {I∧¬b}
{I} while b do S {I∧¬b}
{P} while b do S {Q}
{P} while b do S {Q}
6/49
6/49

Applying the While Rule (schematic proof)
{I∧b} S {I}
{I} while b do S {I∧¬b}
{I∧b} S {I}
{I} while b do S {I∧¬b}
{P} while b do S {Q}
{P} while b do S {Q}
6/49
6/49

Applying the While Rule (schematic proof)
{I∧b} S {I}
{I} while b do S {I∧¬b}
1.{I∧b} S {I}
{I} while b do S {I∧¬b}
{P} while b do S {Q}
{P} while b do S {Q}
6/49
6/49

Applying the While Rule (schematic proof)
{I∧b} S {I}
{I} while b do S {I∧¬b}
1.{I∧b} S {I}
2. {I} while b do S {I ∧ ¬b}
{P} while b do S {Q}
{P} while b do S {Q}
(While Loop, 1)
6/49
6/49

Applying the While Rule (schematic proof)
{I∧b} S {I}
{I} while b do S {I∧¬b}
1.{I∧b} S {I}
2. {I} while b do S {I ∧ ¬b}
I ∧ ¬b → Q
{P} while b do S {Q}
{P} while b do S {Q}
(While Loop, 1)
6/49
6/49

Applying the While Rule (schematic proof)
{I∧b} S {I}
{I} while b do S {I∧¬b}
1.{I∧b} S {I}
2. {I} while b do S {I ∧ ¬b} 3. I ∧ ¬b → Q
{P} while b do S {Q}
{P} while b do S {Q}
(While Loop, 1) (Logic)
6/49
6/49

Applying the While Rule (schematic proof)
{I∧b} S {I}
{I} while b do S {I∧¬b}
1.{I∧b} S {I}
2. {I} while b do S {I ∧ ¬b} 3. I ∧ ¬b → Q
4. {I } while b do S {Q }
{P} while b do S {Q}
{P} while b do S {Q}
(While Loop, 1) (Logic) (Postcondition Weakening, 2, 3)
6/49
6/49

Applying the While Rule (schematic proof)
{I∧b} S {I}
{I} while b do S {I∧¬b}
1.{I∧b} S {I}
2. {I} while b do S {I ∧ ¬b} 3. I ∧ ¬b → Q
4. {I } while b do S {Q }
P→I
{P} while b do S {Q}
{P} while b do S {Q}
(While Loop, 1) (Logic) (Postcondition Weakening, 2, 3)
6/49
6/49

Applying the While Rule (schematic proof)
{I∧b} S {I}
{I} while b do S {I∧¬b}
{P} while b do S {Q}
1.{I∧b} S {I}
2. {I} while b do S {I ∧ ¬b} 3. I ∧ ¬b → Q
4. {I } while
5. P → I
(While Loop, 1) (Logic) (Postcondition Weakening, 2, 3) (Logic)
b
{P} while b do S {Q}
do
S
{Q }
6/49
6/49

Applying the While Rule (schematic proof)
{I∧b} S {I}
{I} while b do S {I∧¬b}
{P} while b do S {Q}
1.{I∧b} S {I}
2. {I} while b do S {I ∧ ¬b}
3. I ∧ ¬b → Q
4. {I } while b
5. P → I
6. {P } while b
(While Loop, 1) (Logic) (Postcondition Weakening, 2, 3) (Logic) (Precondition Strengthening, 4, 5)
do S do S
{Q } {Q }
6/49
6/49

Example
Goal. Find condition I to prove that:
{n>3}while n>0 do n := n-1{n=0}
Observation. Need to prove the above using while-rule, i.e. {I ∧ b} n := n − 1 {I }
{I}while (n>0) do n:= n-1{I∧n≤0} Want. Loop invariant I such that
It is implied by the precondition: n>3→I
if the loop terminates (i.e. n > 0 is false), then I should imply the postcondition:
I∧n≤0→n=0
If I is true and the body is executed, I is true afterwards:
{I ∧ n > 0} n := n − 1 {I }
7/49
7/49

Example (cont.)
Goal. Find condition I to prove that:
{n>3}while n>0 do n := n-1{n=0}
Loop Invariant. I ≡ (n ≥ 0), we have n > 3 → n ≥ 0,
n ≥ 0 ∧ n ≤ 0 → n = 0, and
{n ≥ 0 ∧ n > 0} n := n − 1 {n ≥ 0}.
7/49
7/49

Example, Formally
1. {n−1≥0} n:=n−1 {n≥0}
2. n≥0∧n>0→n−1≥0
3. {n≥0∧n>0} n:=n−1 {n≥0}
4. {n≥0} while(n>0)don:=n−1 {n≥0∧¬(n>0)}(WhileLoop,3)
5. n>3→n≥0
6. {n>3} while(n>0)don:=n−1 {n≥0∧¬(n>0)}
(Logic) (Prec.
Strength., 4, 5)
7. n=0↔n≥0∧¬(n>0)
8. {n≥0} while(n>0)don:=n−1 {n=0}
Other Invariants
e.g. true or n = 0
both are invariants, and give n = 0 as postcondition but n ≥ 0 is better (weaker) as it is more general.
(Logic) (Post. Equiv.,6,7)
(Assignment) (Logic) (Prec. Strength.,1,2)
8/49
8/49

Let’s Prove a Program!
Program (with specification):
{True }
i:=0;
s:=0;
while (i ̸= n) do
i:=i+1;
s:=s+(2*i-1)
{s = n2}
(The sum of the first n odd numbers is n2) Goal: prove
{True} Program {s = n2}
9/49
9/49

A Very Informal Analysis
Let’s look at some examples:
1 = 1 = 12
1+3 = 4 = 22 1+3+5 = 9 = 32 1+3+5+7 = 16 = 42…
It looks OK – let’s see if we can prove it! Goal: prove
{True} Program {s = n2}
10/49
10/49

How can we prove it?
First Task. Find a loop invariant I. (NB: S and s are different!) Post condition and loop condition:
{I∧b} S {I}
{I} while b do S {I∧¬b}
while (i ̸= n) do
i:=i+1; (1, 2, 3, …) s:=s+(2*i-1) (1, 4, 9, …)
{s = n2}
Want. (I ∧ i = n) → (s = n2) to apply postcondweak
Loop Body. Each time i increments, s moves to next square number. Invariant. I ≡ s = i2.
11/49
11/49

Check I as (s = i2) is an invariant: prove {I}S{I} {s=i2} i:=i+1 {Q} {Q} s:=s+(2∗i−1) {s=i2} Seq
{s=i2} i:=i+1;s:=s+(2∗i−1) {s=i2}
Using the assignment axiom and the sequence rule: 1. {Q} s:=s+(2*i-1) {s = i2}
2.
3. {s = i2} i:=i+1 {Q}
4. {s = i2} i:=i+1; s:=s+(2*i-1) {s = i2}
(Sequence, 3, 1)
12/49
12/49

Check I as (s = i2) is an invariant: prove {I}S{I} {s=i2} i:=i+1 {Q} {Q} s:=s+(2∗i−1) {s=i2} Seq
{s=i2} i:=i+1;s:=s+(2∗i−1) {s=i2} Q is {s + (2 ∗ i − 1) = i2}
Using the assignment axiom and the sequence rule: 1. {s + (2 ∗ i − 1) = i2} s:=s+(2*i-1) {s = i2} 2.
3. {s=i2}i:=i+1{s+(2∗i−1)=i2}
4. {s = i2} i:=i+1; s:=s+(2*i-1) {s = i2}
(Assignment)
(Sequence, 3, 1)
13/49
13/49

Check I as (s = i2) is an invariant: prove {I}S{I} {s=i2} i:=i+1 {Q} {Q} s:=s+(2∗i−1) {s=i2} Seq
{s=i2} i:=i+1;s:=s+(2∗i−1) {s=i2} Q is {s + (2 ∗ i − 1) = i2}
Using the assignment axiom and the sequence rule:
1. {s + (2 ∗ i − 1) = i2} s:=s+(2*i-1) {s = i2} (Assignment)
2. {s+(2∗(i+1)−1)=(i+1)2}i:=i+1{s+(2∗i−1)=i2} (Assignment)
3. {s=i2}i:=i+1{s+(2∗i−1)=i2}
4. {s = i2} i:=i+1; s:=s+(2*i-1) {s = i2} So far, so good. (I as (s = i2) is an invariant.)
(Prec. Equiv.,2) (Sequence, 3, 1)
14/49
14/49

Completing the Proof of {True} Program {s = n2} 6 Strengthen the precondition to match the While rule premise
{I ∧b} S {I}
{(s = i2) ∧ (i ̸= n)} i:=i+1; s:=s+(2*i-1) {s = i2}
7 Apply the While rule and postcondition equiv: s = i2 ∧ i = n ↔ s = n2
{s = i2} while … s:=s+(2*i-1) {s = n2} 8 Check that the initialisation establishes the invariant:
{0 = 02} i:=0 {0 = i2} {0 = i2} s:=0 {s = i2} {0 = 02} i:=0; s:=0 {s = i2}
9 (0 = 02) ↔ True, so putting it all together with Sequencing we have {True}i:=0; s:=0; while(i̸=n)doS{s=n2}
15/49
15/49

What about Termination?
Hoare Logic (in this form) proves partial correctness. Example. while 1+1 = 2 do x:=0.
This will loop forever!
can still prove things about it
Exercise.
Termination.
{True} while 1+1 = 2 do x:=0 {False}
remember functional programs? Something must decrease need loop variant (later)
16/49
16/49

Are the Rules Complete?
So far. Have a very simple language
new rules for arrays, for-loops, exceptions, . . .
Focus here. Soundness
every provable Hoare triple is (semantically) true
soundness holds but terms and conditions apply
with these assumptions, also have completeness, i.e. every true Hoare triple is provable.
Completeness. if {P} S {Q} is true then {P} S {Q} is provable
17/49
17/49

What are these Assumptions?
The language we use for expressions in our programs is the same as the language we use in our pre- and postconditions (in our case, basic arithmetic).
We assumed no aliasing of variables. (In most real languages we can have multiple names for the one piece of memory.)
How is aliasing a problem?
18/49
18/49

What are these Assumptions?
The language we use for expressions in our programs is the same as the language we use in our pre- and postconditions (in our case, basic arithmetic).
We assumed no aliasing of variables. (In most real languages we can have multiple names for the one piece of memory.)
How is aliasing a problem?
Suppose x and y refer to the same cell of memory.
􏰎 Weget {y+1=5 ∧ y=5}x:=y+1{x=5 ∧ y=5}(Assignment)
􏰎 i.e. {y=4 ∧ y=5}x:=y+1{x=5 ∧ y=5}
􏰎 i.e. if initial state satisfies False and x:=y+1 terminates then final state
satisfies{x=5 ∧ y=5} (butalsoworksforx=6∧y=6) which makes a mockery of our calculus since it proves rubbish!
18/49
18/49

Finding a Proof
Example.
{ n >= 0 }
f := 1;
i := n;
while (i > 0) do
f := f * i;
i := i-1;
{ f = n! }
19/49
19/49

Finding a Proof
Annotating the program: I =f ∗i!=n!∧i ≥0
{ n >= 0 } f := 1;
{ f = 1 / n >= 0 } — provable with assignment
i := n;
{f=1/i=n/
>=0} –provablewithassignment
==>
{ I}
while (i > 0) do
{ I/i>0}
f := f * i;
i := i-1;
{ I}
— use postcond weakening
— general premise of while rule
— proof obligation for loop body
— n, n * (n-1), n * (n-1) * (n-2) .
— n-1, n-2, n-3, .
— up until here.
— general conclusion of while rule
— use postcond weakening
20/49
{ I
==>
{ f = n! }
/
ot(i>0)}
20/49

From Annotated Programs to Proofs
Initialisation Part
{ n >= 0 } f := 1;
{ f = 1 / n >= 0 } — provable with assignment
i := n;
{f=1/i=n/
>=0} –provablewithassignment
1. {f =1∧n=n∧n≥0}i:=n{f =1∧i =n∧n≥0}(Assignment) 2. {1=1∧n=n∧n≥0}f:=1{f =1∧n=n∧n≥0}(Assignment) 3. n≥0↔1=1∧n=n∧n≥0(Logic)
4. {n≥0}f:=1{f =1∧n=n∧n≥0}(Prec. Equiv. 2,3)
5. {n≥0}f:=1;i:=n{f =1∧i=n∧n≥0}(Sequence,1,4)
21/49
21/49

From Invariant to Loop Body
{ I }
while (i > 0) do
{ I/i>0} f := f * i; i := i-1;
— general premis of while rule
— proof obligation for loop body
— n, n * (n-1), n * (n-1) * (n-2) …
— n-1, n-2, n-3, …
— up until here.
{ I}
{ I / not(i > 0) } — general conclusion of while rule
Invariant. I =f ∗i!=n!∧i ≥0 Loop Body: Proof obligation
{ f * i! = n! / i >= 0 / i > 0 }
f := f * i;
i := i – 1;
{ f * i! = n! / i >= 0}
22/49
22/49

From Annotated Programs to Proofs
Loop Body
{ f * i! = n! / i >= 0 / i > 0 } — proof obligation
for loop body
f := f * i;
{ f * (i-1)! = n! / i >= 0 / i > 0} — new annotation!
i := i-1;
{ f * i! = n! / i >= 0 } — end loop body
6. {f ∗(i −1)! = n!∧(i −1) ≥ 0} i := i−1 {f ∗i! = n!∧i ≥ 0}(Assignment)
7. {(f ∗i)∗(i −1)! = n!∧(i −1) ≥ 0} f := f∗i {f ∗(i −1)! = n!∧(i −1) ≥ 0} (Assignment) 8. f∗i!=n!∧i≥0∧i>0→(f∗i)∗(i−1)!=n!∧(i−1)≥0(Logic)
9. {f∗i!=n!∧i≥0∧i>0}f:=f∗i{f∗(i−1)!=n!∧(i−1)≥0}(Prec.Stren.,7,8)
10. {f∗i!=n!∧i≥0∧i>0}f:=f∗i;i:=i−1{f∗i!=n!∧i≥0}(Sequence,6,9)
23/49
23/49

From Annotated Programs to Proofs
Loop Body to While Loop
{ f * i! = n! / i >= 0 } — premise of while
rule: “I”
while (i > 0) do {f*i!=n!/i>=0/i>0} –“I/”
f := f * i;
i := i-1;
{ f * i! = n! / i >= 0 } — “I”
{ f * i! = n! / i >= 0 / not(i > 0) } — conclusion of while
“I / not b”
11. {f ∗ i! = n! ∧ i ≥ 0}
while (i > 0) do { f:= f*i; i:= i-1}
{f ∗ i! = n! ∧ i ≥ 0 ∧ ¬(i > 0)} (While, 10)
24/49
24/49

Putting it all together
{ n >= 0 }
f := 1;
i := n;
{ f = 1 / i = n / n >= 0}
==>
{ f * i! = n! / i >= 0 }
while (i > 0) do
f := f * i;
— have already
— postcond weakening
i := i-1;
{ f * i! = n! / i >= 0 / not(i > 0) } — have already
==> — postcond weakening
{ f = n! }
12. f = 1 ∧ i = n ∧ n ≥ 0 → f ∗ i! = n! ∧ i ≥ 0 (Logic)
13. {n ≥ 0} f := 1; i := n {f ∗ i ! = n! ∧ i ≥ 0} (Postcond. Weak., 5, 12)
14. {n ≥ 0} program {f ∗ i! = n! ∧ i ≥ 0 ∧ ¬(i > 0)} (Seq., 13, 11)
15. f ∗ i! = n! ∧ i ≥ 0 ∧ ¬(i > 0) → f = n! (Logic)
16. {n ≥ 0} program {f = n!} (Postcondition Weakening, 14, 15)
25/49
25/49

Hoare Logic: Total Correctness
Motto. Total Correctness = partial correctness + termination .
[P] S [Q]
P and Q are precondition and postcondition, as before
S is a code fragment
Meaning. If the precondition holds, then executing S will terminate, and
the postcondition is true.
Example.
[P] S [true] – S always terminates from precondition P {P} S {false} – S never terminates from precondition P
26/49
26/49

Rules for Total Correctness
Q. What are the rules for total correctness? assignment
sequencing
conditional
pre/post strengthening/weakening
still work, as there’s no danger of non-termination. Problematic Rule. while (may introduce non-termination)
27/49
27/49

Assignment, revisited
[Q(e)] x := e [Q(x)] Assumptions. (fine for our toy language) evaluation of expression e terminates.
evaluation of e returns a number (no exception e.g.)
In General.
the expression can be recursively defined there may be errors, e.g. division by zero
28/49
28/49

Rules for Total Correctness
Ps →Pw [Pw]S[Q] [Ps] S [Q]
[P]S[Qs] Qs →Qw [P] S [Qw]
[P] S1 [Q] [Q] S2 [R] [P]S1;S2 [R]
[P ∧b] S1 [Q] [P ∧¬b] S2 [Q] [P]ifbthenS1 elseS2[Q]
(Precondition Strengthening)
(Postcondition Weakening)
(Sequence)
(Conditional)
Assumption. Evaluation of b always terminates (OK here)
29/49
29/49

Termination of Loops
Example
[y > 0]
while (y < r) do r := r - y; q := q + 1 [true] 30/49 30/49 Termination of Loops Example [y > 0]
while (y < r) do r := r - y; q := q + 1 [true] Observations. q := q + 1 irrelevant y doesn’t change, always positive r strictly decreases in each iteration y < r will eventually be false. 31/49 31/49 Termination of Loops: General Condition Example [y > 0]
while (y < r) do r := r - y; q := q + 1 [true] Termination follows if we have a variant E that is, E ≥ 0 at the beginning of each iteration E strictly decreases at each iteration Q. What could be a variant in this example? 32/49 32/49 While Rule for Total Correctness Goal. Show that In Addition to partial correctness (e.g. finding I), find variant E such that E ≥ 0 at the beginning of each iteration: I∧b→E≥0 E is strictly decreasing in each iteration [I ∧ b ∧ (E = n)] S [I ∧ E < n] where n is an auxiliary variable not appearing elsewhere, to “remember” initial value of E [P] while b do S [Q] 33/49 33/49 While Rule for Total Correctness I ∧ b → E ≥ 0 [I ∧ b ∧ E = n] S [I ∧ E < n] [I]while b do S[I∧¬b] where n is an auxiliary variable not appearing elsewhere. Intuition. E is an upper bound to the number of loop iterations termination of functional programs: measure decrease in recursive call 34/49 34/49 Example Goal. [y > 0] while (y < r) do r := r - y; q := q+1 [true] Focus. Loop body r := r - y; q := q + 1 want some invariant: let’s just call it I want some variant: here r is decreasing First Goal. The variant is ≥ 0 when we enter the loop: formally: I ∧ (y < r) → r ≥ 0 this suggests I ≡ y > 0
Second Goal. The invariant is re-established, and the variant decreases formally:
[(y>0)∧(y0)∧r0)∧(y0)∧r 0) ∧ (r < n)] q := q + 1 [y > 0 ∧ r < n] Second Assignment. [(y>0)∧(r−y0∧r0)∧(r−y0∧r0)∧(y0∧r0)∧(r0∧r0)∧(r−y0∧r0)∧(r−y0∧r0)∧(y0)∧(r−y0)∧(y0∧r0)∧(y0]while (y < r) do r:= r-y; q:= q+1[y>0∧y≥r](WhileLoop,5,
6)
8. y >0∧y ≥r →true
9. [y > 0] while (y < r) do r:= r-y; q:= q+1 [true] (Postc. Weak., 7, 8) 37/49 37/49 Second Example [n >= 0]
fact := 1;
i := n;
while (i > 0) do
fact := fact * i;
i := i – 1
[fact = n!]
Q1. What is the invariant (linking n, fact and i)?
before: fact = 1, i = n
1st iteration: fact = n, i = n-1
2nd iteration: fact = n * (n-1), i = n-2

last iteration: fact = n * … * 1, i = 0
Invariant: fact ∗ i! = n!
38/49
38/49

Second Example
[n >= 0]
fact := 1;
i := n;
while (i > 0) do
fact := fact * i;
i := i – 1
[fact = n!]
Q2. Is the invariant fact ∗ i! = n! good enough?
true initially: for fact = 1 and i = n.
implies postcondition: fact ∗ i! = n! ∧ ¬(i > 0) → fact = n!
Stronger Invariant. fact ∗ i! = n! ∧ i ≥ 0
39/49
39/49

Second Example
[n >= 0]
fact := 1;
i := n;
while (i > 0) do
fact := fact * i;
i := i – 1
[fact = n!]
Q3. What’s the variant?
i ≥ 0 for every iteration (I ∧ b → E ≥ 0) decreases with every iteration
Variant. E ≡ i
40/49
40/49

Proof Skeleton
Simple Assignments.
[n >= 0]
fact := 1;
i := n;
[n >= 0 / fact = 1 / i = n]
Applying While
[ fact * i! = n! / i >= 0 ]
while (i > 0) do
fact := fact * i;
i := i – 1
[ fact * i! = n! / i >= 0 / i <= 0] Missing Glue. Weakening / Strengthening from postcondition of assignments to precondition of while from postcondition of while to goal statement (fact = n!) 41/49 41/49 Zooming in on While [ fact * i! = n! / i >= 0 ]
while (i > 0) do
fact := fact * i;
i := i – 1
[ fact * i! = n! / i >= 0 / i <= 0] Loop Body (Invariant: fact ∗ i! = n! ∧ i ≥ 0, Variant: i) [fact * i! = n! / i >= 0 / i > 0 / i = a]
fact := fact * i;
i := i – 1
[ fact * i! = n! / i >= 0 / i < a] Positivity Condition. fact ∗ i! = n! ∧ i ≥ 0 ∧ i > 0 → i ≥ 0 (Maths)
42/49
42/49

While Rule: Soundness
I ∧ b → E ≥ 0 [I ∧ b ∧ E = n] S [I ∧ E < n] [I]while b do S[I∧¬b] Partial Correctness. premises of the rule imply those of the rule for partial correctness so if the loop terminates, the postcondition holds Missing. Termination 43/49 43/49 Termination Analysis I ∧ b → E ≥ 0 [I ∧ b ∧ E = n] S [I ∧ E < n] [I]while b do S[I∧¬b] Let σ be a state that validates the precondition I. If b is false in σ, we are done. Assumethatbistrueinσ,hencethevalueofE inσis≥0. Induction on the value σ(E) of E in state σ. Base case. σ(E) = 0. Right premise implies that E < 0 after one iteration With left premise, get that ¬b after one iteration hence the loop terminates after one iteration. Step Case. Let σ(E) = k + 1 after one iteration, have σ(E) ≤ k statement follows by induction hypothesis. 44/49 44/49 Variation: More Expressive Logic So far. In triples {P} S {Q} we have S a program fragment (we keep this for now) P and Q propositional formulae made from basic arithmetic Q. How about expressing the following? {true} x := 2 ∗ x {even(x)} A. We could say that even(x) = ∃y.2 ∗ y = x Change. Allowing pre/postconditions to be first order formulae. 45/49 45/49 Example. {true} x := 2 ∗ x {∃y.2 ∗ y = x} Using the assignment axiom. {∃y.2 ∗ y = 2 ∗ x} x := 2 ∗ x {∃y.2 ∗ y = x} More Expressive Logic. Assertions are first-order formulae all rules remain valid Hoare-logic is (almost) insensitive to underlying logic 46/49 46/49 Variation: More Expressive Programs Example Feature. Arrays allow expressions to contain a[i] (we assume that the index is always in scope) Maximum Finding m := a[0] i := 1; while (i < n) do if a[i] > m then m := a[i] else m := m;
i := i + 1
Q. How do we express that m is the maximum array element?
A. Use first order logic.
mislargest: ∀k.0≤k= 1}
m := a[0]
i := 1;
{m = a[0] / i = 1 / n >= 1 }
==>
{forall k. 0 <= k < i -> m >= a[k] / i <= n} while (i < n) do if a[i] > m then m := a[i] else m := m;
i := i + 1
{forall k. 0 <= k < i -> m >= a[k] / i <= n / i >= n}
==>
{forall k. 0 <= k < n -> m <= a[k]} Invariant. I ≡ ∀k.0 ≤ k < i → m ≥ a[k] ∧ i ≤ n initially: m=a[0]∧i =1→I at end: I ∧ i ≥ n → ∀k.0 ≤ k < n → m ≤ a[i] Remark. Can turn this into a formal proof as before. 48/49 48/49 References The textbook has material on Hoare Logic Grassman & Tremblay, “Logic and Discrete Mathematics: A Computer Science Perspective”, Prentice-Hall, Chapter 9, pp. 481-518. Some nice online notes with lots of examples: Gordon, “Specification and Verification I”, http://www.cl.cam.ac. uk/~mjcg/Lectures/SpecVer1/SpecVer1.html, Chapters 1-2, pp. 7-46. A comprehensive early history of Hoare Logic appears in Apt, K.R., Ten Years of Hoare Logic: A Survey”, ACM Transactions on Programming Languages and Systems, October, 1981. 49/49 49/49

Leave a Reply

Your email address will not be published. Required fields are marked *